1999
DOI: 10.1046/j.1523-1755.1999.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral ureteral obstruction impairs renal antioxidant enzyme activation during sodium depletion

Abstract: In summary, sodium depletion increased several renal antioxidant enzymes, consistent with a stress response to increased ROS production. Further, UUO not only reduced antioxidant enzyme activities but also inhibited increases seen with sodium depletion. We conclude that suppression of renal antioxidant enzyme activities by UUO contributes to the progression of renal injury in obstructive nephropathy, a process exacerbated by sodium depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Most interesting was the finding that stretching proximal tubular cells in vitro suppressed catalase expression, suggesting that mechanical forces imposed on tubular epithelial cells in the obstructed kidney could contribute to renal oxidant injury [90]. Since obstructive nephropathy can result in significant sodium wasting and volume contraction, we examined the effect of sodium depletion on renal antioxidant enzyme activity in rats subjected to chronic UUO [91]. We found that while sodium depletion increased several renal antioxidant enzymes in intact rats, UUO not only reduced baseline antioxidant activities, but also prevented the normal response to sodium depletion [91].…”
Section: Progressive Renal Injury Resulting From Urinary Tract Obstrumentioning
confidence: 99%
“…Most interesting was the finding that stretching proximal tubular cells in vitro suppressed catalase expression, suggesting that mechanical forces imposed on tubular epithelial cells in the obstructed kidney could contribute to renal oxidant injury [90]. Since obstructive nephropathy can result in significant sodium wasting and volume contraction, we examined the effect of sodium depletion on renal antioxidant enzyme activity in rats subjected to chronic UUO [91]. We found that while sodium depletion increased several renal antioxidant enzymes in intact rats, UUO not only reduced baseline antioxidant activities, but also prevented the normal response to sodium depletion [91].…”
Section: Progressive Renal Injury Resulting From Urinary Tract Obstrumentioning
confidence: 99%
“…Tissue GPx activity increased in almost all groups compared to the sham groups. Kinter et al showed that increased sodium wasting in rats in which they induced unilateral CUO did not change antioxidant enzyme CAT levels but did cause a slight increase in GPx (14).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is believed to mediate a wide range of kidney disorders, including renal impairment, acute renal failure [18,19], obstructive nephropathy [20], hyperlipidemia [21] and glomerular damage [22]. As HT and its metabolites have been shown to be present in the kidney in relatively high amounts [15], and express antioxidant activity in vitro and in vivo [23][24][25][26][27][28], they may be able to exert a degree of protection against oxidative kidney injury.…”
Section: Introductionmentioning
confidence: 99%